(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to measure the impact of domestic and foreign direct investment, along with other factors, most notably the value of Saudi exports, on the economic growth rate during the period 1990-2023. This study used econometric analysis and estimated the proposed model consisting of three behavioral equations. The results showed that a 10% increase in the value of estimated domestic investments, estimated foreign direct investments, and the total value of Saudi exports leads to an increase in the economic growth rate by 1.16%, 2.78%, and 12.87%, respectively. In light of the factors determining both domestic and foreign direct investment, a gradual decline in these investments is expected through 2030. Despite the decline in domestic and foreign investments, the increase in the value of Saudi exports from SAR 2,098.5 billion in 2025 to SAR 3,023.0 billion in 2030 will lead to an increase in the Kingdom of Saudi Arabia’s economic growth rate from 5.0% in 2025 to 7.3% in 2030. To achieve the targeted economic growth rate, it is necessary to maintain domestic and foreign direct investment rates and increase the value of Saudi exports of goods and services until they reach SAR 3,023.0 billion in 2030.